Meningkatkan Kemampuan Mengabstraksi Teks Prosedur Kompleks Menggunakan Model Pembelajaran Inquiry - Murtiani, Ni Nyoman (Universitas Pendidikan Ganesha, 2018)
This research was conducted in Dwijendra Gianyar High School for the X grade students in the even semester of the 2015/2016 academic year whose ability to abstract complex procedure texts was very far below the Minimum Completion Criteria (KKM) value. The purpose of this class action research is to determine whether the ability to abstract complex procedure texts can be improved through the use of Inquiry learning models. The subjects of this study were the X grade students in the even semester of the academic year 2015/2016 Dwijendra Gianyar High School totaling 45 people. The data collection method is a test of learning outcomes. The data analysis method is descriptive. The results obtained from this study are that the ability to abstract complex procedure texts can be improved through the use of Inquiry learning models. This is evident from the results obtained initially at 63.64, in the first cycle to 72.64 and in the second cycle to 79.24. The conclusion obtained from this study is the ability to abstract complex procedure texts of class X students in the even semester of the 2015/2016 academic year Dwijendra Gianyar High School can be improved through the use of Inquiry learning model.